Myc‐dependent endothelial proliferation is controlled by phosphotyrosine 1212 in VEGF receptor‐2. (6th May 2020) - Testini, Chiara; Smith, Ross O; Jin, Yi; Martinsson, Pernilla; Sun, Ying; Hedlund, Marie; Sáinz‐Jaspeado, Miguel; Shibuya, Masabumi; Hellström, Mats; Claesson‐Welsh, Lena
Abstract :